Targeted modulation of intestinal barrier and mucosal immune-related microbiota attenuates IgA nephropathy progression - Ran Zhang; Yuyan Tang; Xiangru Feng; Xiaoxuan Lu; Mengyao Zhao; Jiayang Jin; Xiaoguo Ji; Haidong He; Liming Zhao (Gut Microbes)
IgA nephropathy (IgAN) is related to the balance of gut microbiota. However, it is unclear whether changes in the gut microbiota can cause IgAN or attenuate its progression. This study employed IgAN and human microbiota-associated (HMA)-IgAN models to investigate the impact of IgAN on gut microbiota alteration and the mechanisms by which gut microbiota might trigger IgAN. Furthermore, this study examined the effects of chitooligosaccharides (COS) and COS formulation (COSF) with microbiota-targeting function on enhancing intestinal barrier and renal functions. These results revealed that IgAN led to a reduction in α-diversity and structural alterations in the gut microbiota, characterized by an increase in Shigella sonnei, Streptococcus danieliae, Desulfovibrio fairfieldensis, and a decrease in Bifidobacterium pseudolongum and Clostridium leptum. There was also an imbalance in intestinal B-cell immunity and a decrease in the level of tight junction proteins (ZO-1 and Occludin). Intestinal barrier and mucosal immune-related microbiota (Clostridium leptum, unclassified Lachnospiraceae NK4Al36 group, unclassified Clostridia vadinBB60 group, unclassified Oscillospiraceae, and unclassified Roseburia) were enriched through targeted modulation with COS/COSF, enhancing intestinal ZO-1 expression and reducing APRIL/BAFF overexpression, thereby reducing renal damage in IgAN. In conclusion, this study clarified the kidney-gut crosstalk between gut microbiota and IgAN, providing scientific evidence for developing microbiota-targeted food interventions to improve IgAN outcomes.